Pengaruh Insentif, Locus of control, dan Efikasi diri terhadap Efektivitas Kinerja Karyawan Di PT. Harapan Sejahtera Karya Utama Candi Sidoarjo - Fajar Mahendra; Dewi Andriani (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to determine and analyze the partial influence of Locus of Control on self-efficacy incentives on the effectiveness of employee performance job satisfaction on self-efficacy. with the population of employees of PT. Harapan Sejahtera Karya Utama has 69 employees. This study uses a sampling technique using a total sampling technique with a total of 69 respondents. Data analysis techniques used are primary data obtained from questionnaires that are distributed, while secondary data are sourced from articles,journals,and books that are references to this research. Based on the results of the study, it was found that Locus of Control has a positive and significant influence on the effectiveness of employee performance of PT. Harapan Sejahtera Karya Utama . Incentives have a positive and significant influence on the effectiveness of employee performance PT. Harapan Sejahtera Karya Utama. Job satisfaction has a positive and significant influence on the self-efficacy of PT. Harapan Sejahtera Karya Utama.In addition, in this context Locus of Control, incentives and job satisfaction simultaneously also proved to have a significant influence on the effectiveness of employee performance PT. Hope Of Success).